Evaluation of the Implementation of the International Credit Transfer Program of Makassar State University - Suardi, Izzul Kiram; Arnidah, Arnidah; Haling, Abdul (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
In 2021, Universitas Negeri Makassar (UNM) first became one of the universities participating in the International Credit Transfer Program (ICT) and made Universiti Kebangsaan Malaysia (UKM) one of the partner universities. Thus, this study aims to evaluate the implementation of ICT held online by UNM for one semester. The evaluation model used in this study is an illuminative evaluation model that focuses on qualitative data collection using observation, interview, and document review methods. The results showed that the implementation of ICT by UNM went quite well. This is evidenced by the achievement of the goals of the ICT program for universities and students. In addition, this program motivates students to take part in other international programs participated in by UNM and organized by the government. However, there are some problems encountered by UNM and students during the program. Such as communication problems of the committee and participants, to administrative problems. In conclusion, ICT is incredibly good to be followed again by UNM, seeing the magnitude of the impact and enthusiasm of the students. However, improvements to the administrative and communication systems must be completed first before returning to participate in the following years.